2016
DOI: 10.1002/chem.201601213
|View full text |Cite
|
Sign up to set email alerts
|

η6‐Arene‐Zirconium‐PNP‐Pincer Complexes: Mechanism of Their Hydrogenolytic Formation and Their Reactivity as Zirconium(II) Synthons

Abstract: The cyclometalated monobenzyl complexes [(Cbzdiphos(R) -CH)ZrBnX] 1 (iPr) Cl and 1 (Ph) I reacted with dihydrogen (10 bar) to yield the η(6) -toluene complexes [(Cbzdiphos(R) )Zr(η(6) -tol)X] 2 (iPr) Cl and 2 (Ph) I (cbzdiphos=1,8-bis(phosphino)-3,6-di-tert-butyl-9H-carbazole). The arene complexes were also found to be directly accessible from the triiodide [(Cbzdiphos(Ph) )ZrI3 ] through an in situ reaction with a dibenzylmagnesium reagent and subsequent hydrogenolysis, as exemplified for the η(6) -mesitylene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 130 publications
0
22
0
1
Order By: Relevance
“…[6] In addition, hole-transporting carbazole groups have been introduced into the core of ligands coordinated to ap hosphorescent transition-metal emitter to reduce the energyb arrierf or hole injection and to decrease triplet-triplet annihilation. Four approachesh ave been developed to achieve this:1 )The direct use of carbazoles as amide ligands to form homoleptic low-coordinate transition-metal complexes; [7] 2) carbazolide groups used as central anionic linkersi nC ,N,C, [8] P, N,P, [9] and N,N,N pincers [10] based on bis(NHC), bis(phosphine), and bis(imino)l igands;3 )chelate-supported metalated carbazole groups formingf ive- [11] and six-membered [12] heterometallacycles; 4) carbazole groups used as peripherala rylamine substituentso fc oordinated bidentate ligandsi nh omo-a nd heteroleptic complexes. [13] However,a sf ar as we know,c omplexes containing ac arbazole groupc oordinated as an h 1 -arene are unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…[6] In addition, hole-transporting carbazole groups have been introduced into the core of ligands coordinated to ap hosphorescent transition-metal emitter to reduce the energyb arrierf or hole injection and to decrease triplet-triplet annihilation. Four approachesh ave been developed to achieve this:1 )The direct use of carbazoles as amide ligands to form homoleptic low-coordinate transition-metal complexes; [7] 2) carbazolide groups used as central anionic linkersi nC ,N,C, [8] P, N,P, [9] and N,N,N pincers [10] based on bis(NHC), bis(phosphine), and bis(imino)l igands;3 )chelate-supported metalated carbazole groups formingf ive- [11] and six-membered [12] heterometallacycles; 4) carbazole groups used as peripherala rylamine substituentso fc oordinated bidentate ligandsi nh omo-a nd heteroleptic complexes. [13] However,a sf ar as we know,c omplexes containing ac arbazole groupc oordinated as an h 1 -arene are unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…The groups of Gade, Nishibayashi and Hou have shown that N ‐heterocyclic PNP pincer complexes of the group 4 metals may be employed for the activation of substituted pyridines, and dinitrogen,, respectively. Using the carbazole‐based CbzC ( R PNP) ligand, the zirconium cyclohexadiene‐1,4‐diido complexes 28 (X = Cl, I) have been isolated (see Scheme ) via cyclometalated intermediates, which will be discussed in more detail below (Scheme ) , , . Although the zircona‐norbornadiene structure depicted in Scheme was found to be slightly more stable than the corresponding zirconium(II) η 6 ‐arene isomer, it was shown that complexes 28 (R = i Pr with X = Cl, R = Ph with X = I) are valuable zirconium(II) precursors for the in situ generation of CbzC ( R PNP)Zr II X building blocks.…”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 99%
“…Although the zircona‐norbornadiene structure depicted in Scheme was found to be slightly more stable than the corresponding zirconium(II) η 6 ‐arene isomer, it was shown that complexes 28 (R = i Pr with X = Cl, R = Ph with X = I) are valuable zirconium(II) precursors for the in situ generation of CbzC ( R PNP)Zr II X building blocks. The rare zirconium(II) isocyanide derivative 29 , for example, was prepared starting from 28 (see Scheme ) . Complex 28 was also shown to react cleanly with 4‐substituted pyridines to afford the corresponding bipyridine derivatives 30 via dehydrogenative C–C coupling.…”
Section: Pnp Pincers and Their Reactivity Patternsmentioning
confidence: 99%
See 2 more Smart Citations